Towards possible application of quantum magnetometers in nuclear magnetic logging tools - A.S. Alexandrov; M.M. Doroginzkii; M.S. Tagirov; V.D. Skirda (Учёные записки Казанского университета: Серия Физико-математические науки)
One of the key problems of nuclear magnetic logging (NML) is the low sensitivity. As long ago as 1991, it was proposed to use superconducting quantum interferometers (SQUID) to increase the signal-to-noise ratio in the NMR logging devices. However, this possibility has not yet been realized due to the difficulty in creating and maintaining low temperatures (required for SQUID operation) in the well conditions. The paper considers the possibilities of increasing the signal-to-noise ratio in the NMR logging equipment taking into account new advances in the field of SQUID NMR and the recently developed SQUIDs on high-temperature superconductors (HTSC). The estimates of the gain in sensitivity owing to the use of the SQUID as a preamplifier for recording the NMR signal have been carried out. It has been shown that a preamplifier based on a SQUID can give a gain of 100 or more times at resonance frequencies up to 700 kHz.